Preserving nutritional, visual, and functional quality of thermally processed low-acid canned foods for dogs and cats - Dainton, Amanda Nicole (Kansas State University, 2021)
Limited published research has addressed the quality of canned pet food. Detailed information regarding these thermally processed foods is needed. Specific concerns include functionality of carbohydrate hydrocolloids, discoloration due to supplemental copper, and thiamine degradation due to thermal processing. An experiment with the following treatments was conducted to evaluate how carbohydrate hydrocolloids affect heat penetration, color, and texture of canned pet food: 1% dextrose (D), 0.5% guar gum and 0.5% dextrose (DG), and 0.5% guar gum with either 0.5% kappa carrageenan (KCG), 0.5% locust bean gum (LBG), or 0.5% xanthan gum (XGG). The D treatment had the thinnest (P < 0.05) batter consistency (23.64 cm/30 sec), the greatest (P < 0.05) lethality (20.24 min), and the lowest (P < 0.05) finished product toughness (67 Nｘmm). The DG treatment had thicker (P < 0.05) batter consistency (6.6 cm/30 sec), increased (P < 0.05) toughness (117 Nｘmm), and decreased (P < 0.05) lethality (18.63 min) and expressible moisture (26.93%) compared to D. The KCG, LBG, and XGG treatments were the thickest (average 2.75 cm/30 sec; P < 0.05) treatments pre-thermal processing with lethality comparable (P > 0.05) to DG. The KCG treatment was firmer (27.00 N; P < 0.05) and tougher (370 Nｘmm; P < 0.05) than LBG and XGG (average 15.59 N and 235 Nｘmm, respectively), but contained more (P < 0.05) expressible moisture (23.59% vs average 16.54%, respectively). The addition of carbohydrate hydrocolloids thickened pre-retort batters and lowered lethality. Further, guar gum with either xanthan gum or locust bean gum created softer textures with greater water holding capacities compared to products with kappa carrageenan and guar gum. Two experiments were conducted to determine the effect of alternative copper sources on the development of off-colors and black blemishes. In the first experiment, a no added copper control (NC) was compared to copper-lysine-glutamate at 60 and 300 mg/kg dry matter (DM) (LG60 and LG300, respectively), copper amino acid complex at 60 and 300 mg/kg DM (CA60 and CA300, respectively), and copper sulfate at 60 and 300 mg/kg DM (CS60 and CS300, respectively). Addition of copper darkened (average L* 47.57; P < 0.05), decreased (P < 0.05) red (average a* 2.07) and yellow hues (average b* 9.20), and lowered (P < 0.05) the vitamin E content (average 211 mg/kg DM) compared to NC (55.4, 8.43, 17.20 and 252 mg/kg DM, respectively). Treatments did not affect (P > 0.05) vitamins A or B1 or fatty acid profiles. A second experiment included the following treatments compared to NC: copper-glutamate at 6 and 12 mg/kg DM (CG6 and CG12, respectively), copper amino acid complex at 6 and 12 mg/kg DM (CA6 and CA12, respectively), and copper sulfate at 6 and 12 mg/kg DM (CS6 and CS12, respectively). Addition of copper decreased (P < 0.05) red and yellow hues, with the exception of the similar (P > 0.05) yellow scores for NC (19.22) and CG6 (18.18). Vitamin E generally decreased (P < 0.05) with the addition of copper, except for NC and CS12, which were similar (P > 0.05) to each other (average 111.89 mg/kg DM). The number of blemishes was greatest (P < 0.05) for CG6 and CG12 (average 4.05 blemishes/slice). Copper amino acid complex may be a suitable alternative to copper sulfate at lower levels (i.e. 6 and 12 mg/kg DM), as these two sources exhibited similar color hues and number of blemishes. An experiment was conducted to evaluate dried yeasts as sources of thiamine that may survive thermal processing of a canned cat food. There were 2 levels of vitamin premix (with or without) and four sources of yeast: no yeast (NY), Lalmin B-Complex Vitamins (LBV), a spray dried yeast from The Peterson Company (BY), and BGY Advantage (EA). Treatments containing BY (-33.8 mg/kg DM) exhibited similar (P > 0.05) processing losses of thiamine compared to those with NY (-31.3 mg/kg DM), while EA (-40.5 mg/kg DM) and LBV (-55.6 mg/kg DM) were both greater (P < 0.05) than NY. All treatments exhibited similar (P > 0.05) processing losses of thiamine compared to the treatment containing the vitamin premix at standard commercial levels without any yeast. Thiamine loss for BY was consistent with standard ingredients (including vitamin premix) used in canned cat food. As such, the BY yeast may be an acceptable thiamine source for canned cat foods. Overall, the quality of canned pet food is influenced by ingredient composition and the thermal process. The results from this dissertation provide insight regarding ingredient and processing interactions on commercial canned pet food.
Keywords: Canned pet food; Copper; Hydrocolloid; Thermal processing; Thiamine; Wet pet food